Divine Logos and Translation among Iberian Muslims: From Ibn Ḥazm (d. 456H/1064CE) to Aḥmad al-Ḥanafī (d. 1049H/1650CE) - Mònica Colominas Aparicio (Religions, 2021)
Like other religious traditions, Islam has accommodated notions of the divine logos. The actual elaboration of these notions has been heavily dependent on how the translation of God’s word and commandments to humans were understood as an object of intra-community debate, as well as in polemics with non-Muslims (inter-community debate). These two debates converged in the Muslim critique of the translation, transmission, and interpretation of the divine logos by Jews and Christians in their scriptures, although such convergence took different forms in different historical settings. The present contribution focuses on several examples of the engagement of Muslims with the Bible in the medieval Iberian Peninsula and in exile. The choice of authors and works ranges from the 11th-century Andalusī scholar Ibn Ḥazm to the exile Aḥmad al-Ḥanafī (d. 1049H/1650CE). It is nevertheless not intended as a comprehensive overview of Muslim approaches from the Western Mediterranean region. The objective is rather to discuss several aspects associated with the translation of the divine logos in polemics as a tool of identity that is intimately related to Muslim practices of exegesis and transmission of the Jewish and Christian writings. Particular attention is directed toward the broader issue of how notions of the translation of God’s word have been informed by language practices within contexts of inter-religious contact and competition (either between existing social bodies or as references to a relatively recent past). A preliminary look at Muslim modes of scriptural interpretation suggests that translation and exegesis, as well as the ways in which Muslims understood these practices as performed by non-Muslims, were part of a tradition that took final form and meaning, and that was subject to change when re-enacted in specific contexts. Any understanding of the subject must be read against the backdrop of Muslim configurations of knowledge within the local communities, as combined with tradition.